Laser textured dimple-patterns to govern the surface wettability of superhydrophobic aluminum plates - Tong, Wei; Cui, Lingling; Qiu, Rongxian; Yan, Chengqi; Liu, Yuntong; Wang, Nan; Xiong, Dangsheng (Journal of materials science & technology, 2021)
[Display omitted] •The surface wettability of the superhydrophobic samples is regulated by controlling the dimple-pattern dimensions during the laser processing.•A fluorescence method is utilized to record the zones on the superhydrophobic surface penetrated by small enough water molecules.•Such a fluorescence method can intuitively display the air trapping ability of the superhydrophobic surface.•Laser-textured superhydrophobic samples show strong mechanical stability in comparison with bare aluminum alloy. A laser texturing technique herein can endow bare aluminum alloy surface with regular dimple-pattern array and thus generates a case hardening. After STA treatment, these laser-textured samples become superhydrophobic. The surface wettability of the laser-textured samples can be regulated by controlling the dimple-pattern dimensions during the laser processing. It is noteworthy that a fluorescence method is utilized to record the zones on the superhydrophobic surface penetrated by small enough water molecules. Compared with a general method of the Cassie-Baxter theoretical calculation, this fluorescence method intuitively exhibits the air trapping ability of the superhydrophobic surface. Furthermore, the laser-textured superhydrophobic samples have a notable hysteresis phenomenon at the initial period of UMT friction because the air cushion trapped within superhydrophobic samples have strong repellency against water droplets on the hydrophilic steel ball. Additionally, such samples display strong mechanical stability in comparison with bare aluminum alloy because of the presence of case hardening on the surface of the laser patterns. The research results above provide a valuable reference for designing a surface with different wettability, which may inspire practical applications in the fields of fluid transport, droplet manipulation, water harvesting and microfluidic devices.